Stomach cancer detection using CIELAB color space - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
Stomach cancer is the fourth most common cancer in the world. In addition, this type of cancer ratio is increasing in Turkey. Therefore, in this study, results of preliminary studies of a vision-based approach is presented. In this approach, RGB - CIELAB color space conversion method is applied to the endoscopy images in the data set by using MATLAB software platform. Preliminary results indicate that the applicability of the CIELAB conversion method in the detection of gastric cancer yields satisfactory results and that computer assisted systems can be developed to assist specialists. © 2019 IEEE.
Keywords: Biomedical image processing; CIELAB color space; Image segmentation; Stomach cancer